PEMBANGKIT LISTRIK TENAGA SURYA FOTOVOLTAIK SEBAGAI ENERGI BARU DAN TERBARUKAN PELUANG SERTA KENDALA - Kurnia, Ahmad (Jurnal TEDC, 2025)
Solar energy as new and renewable energy (NRE) in Indonesia has great potential, reaching 4800 watt-hours/m2 per day because Indonesia's geography is in the tropics. Therefore, its use for direct electricity generation with environmentally friendly photovoltaic effects has received great attention from the government and the public. This article describes the development of the use of photovoltaic solar energy, its working principles, efficiency and how photovoltaic electricity is becoming an energy source that is increasingly developing today. World photovoltaic solar power generation (PLTS) in 1996 was only 0.3 GWatt to 303 GWatt in 2016, an increase of 1000 times in 20 years. The efficiency of photovoltaic systems has increased from 6% in the 1950s, now reaching 20%. In Indonesia, in 2021, photovoltaic electricity will contribute 1.8% of New and Renewable Energy (EBT), which consists of hydro, geothermal, wind and biomass energy. In 2025, it is targeted to contribute 22% of EBT after the Bintan PLTS mega project with a capacity of 3.5 GWatt operates, part of which will be exported. Photovoltaic solar energy has large and significant potential to be used as a long-term alternative energy source in the future and can be transmitted more efficiently. Meanwhile, operational cost constraints for residential PLTS are reduced by synergy with the PLN electricity network with On-Grid installations, which saves the cost of batteries, which are still high in price, besides electricity can be sent to PLN.